Economic Growth and Its Determinants in Pakistan (The Pakistan Development Review, 2008)
Economically developed countries have been able to reduce their poverty level, strengthen their social and political institutions, improve their quality of life, preserve natural environments and achieve political stability [Barro (1996); Easterly (1999); Dollar and Kraay (2002a); Fajnzylber, Lederman, et al. (2002)]. After the World War II, most of the countries adopted aggressive economic policies to improve the growth rate of real gross domestic product (GDP). The neoclassical growth models imply that during the evolution between steady states; technology, exogenous rate of savings, population growth and technical progress generate higher growth levels [Solow (1956)]. Endogenous growth model developed by Romer (1986) and Lucas (1988) argue that permanent increase in growth rate depends on the assumption of constant and increasing returns to capital.1 Similarly, Barro and Lee (1994) investigate the empirical association between human capital and economic growth. They seem to support endogenous growth model by Romer (1990) that highlight the role of human capital in economic activity. Fischer (1993) argues that long-term growth is negatively linked with inflation and positively correlated with better fiscal performance and factual foreign exchange markets. In the context of developing countries, investment both in capital and human capital, labour force, ability to adapt technological changes, open trade polices and low inflation are necessary for economic growth.